Identification of Bean Lines (Phaseolus vulgaris) with Low Genotype–Environment Interactions Under Rainfed in Two Semiarid Sites of North-Central Mexico - José Ángel Cid-Ríos; Jorge Alberto Acosta-Gallegos; Francisco Guadalupe Echavarría-Cháirez; Rómulo Bañuelos-Valenzuela; Alejandro Antonio Prado-García (Agronomy)
The seed yield of 28 bean (Phaseolus vulgaris) lines from different crosses and two check cultivars was evaluated under rainfed conditions in two sites in North-Central Mexico. The aim was to identify high-yielding lines with low genotype–environment interactions (GEIs). Trials were conducted under a 6 × 5 square lattice design with four replicates; due to the lack of rainfall in Zacatecas, the trial was helped with supplemental irrigation. Data were analyzed by location and combined to determine the effects of GEIs using the additive main effects and multiplicative interaction model (AMMI) model. The combined analysis showed that 75.45% of the yield variation among lines was due to the effect of the environment, 11.75% was due to genotypes, and 12.79% was due to GEIs. Lines 5 and 10 displayed the highest yield, which slightly surpassed the checks (2.1 and 0.11%, respectively) and showed greater stability than those in the test environments. The AMMI analysis allowed for the selection of stable and high-yielding lines under drought conditions. Data on the weight and yield per hectare of a hundred seeds between and within locations identified lines 5, 10, and 16 as outstanding and capable of being used as a parent in a future hybridization program or as a new cultivar with drought tolerance.